2016
DOI: 10.1002/pds.4059
|View full text |Cite
|
Sign up to set email alerts
|

The impact of adherence to inhaled drugs on 5‐year survival in COPD patients: a time dependent approach

Abstract: PurposeWhether inhaled medications improve long‐term survival in Chronic Obstructive Pulmonary Disease (COPD) is an open question. The purpose of this study is to assess the impact of adherence to inhaled drug use on 5‐year survival in COPD.MethodsA population‐based cohort study in three Italian regions was conducted using healthcare linked datasets (hospitalization, mortality, drugs). Individuals (45+ years) discharged after COPD exacerbation in 2006–2009 were enrolled. Inhaled drug daily use during 5‐year fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
27
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 54 publications
0
27
0
4
Order By: Relevance
“…Adherence is defined as the process by which patients take their medications as prescribed, comprising 1) initiation of treatment, 2) implementation of the dosing regimen, and 3) persistence with treatment 3. Previous literature has demonstrated that poor adherence can exist among patients with asthma or COPD46 and has an impact on disease outcomes 79. Contributing factors to poor adherence at the patient level include perceived need of treatment,10 fear of side effects,11 and ability to use inhaler devices correctly 12,13.…”
Section: Introductionmentioning
confidence: 99%
“…Adherence is defined as the process by which patients take their medications as prescribed, comprising 1) initiation of treatment, 2) implementation of the dosing regimen, and 3) persistence with treatment 3. Previous literature has demonstrated that poor adherence can exist among patients with asthma or COPD46 and has an impact on disease outcomes 79. Contributing factors to poor adherence at the patient level include perceived need of treatment,10 fear of side effects,11 and ability to use inhaler devices correctly 12,13.…”
Section: Introductionmentioning
confidence: 99%
“…12,14 Four studies assessed adherence in a single measurement over the entire exposure period, 10,14,15,17,20 whereas the remainder used a time-varying approach by breaking the exposure period into intervals that ranged between one-quarter and 3 years. [11][12][13]16,18,19,21 Despite this wide range of work in which PDC or a similar measure was used to estimate the association between adherence and mortality, we were not able to find any studies that assessed whether these measures could produce biased results in some situations. We hypothesized that the outcome event (mortality) could bias the adherence measurement if patient deaths occur during the exposure measurement period.…”
mentioning
confidence: 97%
“…PDC and similar measures have been widely used in studies to assess the association between adherence and mortality . These studies used a variety of designs; eight of them established a separate adherence exposure period and excluded patients who died prior to its end date .…”
mentioning
confidence: 99%
See 2 more Smart Citations